2002
DOI: 10.1021/cm010756c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Oligo(oxyethylene)-Derivatized Poly(3,4-ethylenedioxythiophenes):  Cation-Responsive Optoelectroelectrochemical Properties and Solid-State Chromism

Abstract: Electroactive π-conjugated polymers have been synthesized by electrochemical polymerization of precursors consisting of two (3,4-ethylenedioxythiophene) (EDOT) groups linked by oligo(oxyethylene) chains of variable length. The analysis of the cyclic voltammetric behavior in the presence of various cations (Bu4N+, Li+, Na+, Ca2+, Sr2+, and Ba2+) shows that the nature and charge of the electrolyte cation exert a considerable influence on the potential of the anodic peak associated with the oxidation of the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 27 publications
1
81
0
1
Order By: Relevance
“…23 According to our previous results on PEDOT-based modified electrodes, 24 we describe here the synthesis of a novel hydroxysuccinimidyl ester derivative of EDOT, 1, and the electrochemical copolymerization of 1 and the bis-EDOT compound, 2 (Scheme 1). 25 It is shown that a redox signal corresponding to the ferrocene units appear upon covalent immobilization of ferrocene-ODN assemblies via amide bond formation, which directly confirm, the probes grafting.…”
Section: Introductionmentioning
confidence: 54%
“…23 According to our previous results on PEDOT-based modified electrodes, 24 we describe here the synthesis of a novel hydroxysuccinimidyl ester derivative of EDOT, 1, and the electrochemical copolymerization of 1 and the bis-EDOT compound, 2 (Scheme 1). 25 It is shown that a redox signal corresponding to the ferrocene units appear upon covalent immobilization of ferrocene-ODN assemblies via amide bond formation, which directly confirm, the probes grafting.…”
Section: Introductionmentioning
confidence: 54%
“…[7][8][9] Ko et al [10] associated an electrochromic viologen with EDOT; however, the route of derivatizing the monomer and its further polymerization are rather complicated processes. Similarly, post-polymerization functionalization of PEDOT has also been done [11] but there is a paucity of reports wherein electrochromic efficiency of such derivatized polymers has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of research work has also been devoted to covalent binding of recognition sites, like crown ethers [87 ± 98], benzo-crown ether [99], cyclam (tetraazamacrocycle) [100,101], glucose oxidase [102], cyclodextrin [103], aza crown ethers [104,105], calixarenes [106 ± 108], ferrocene crown ether [109], porphyrin [110], oligo(oxyethylene) [111,112], nucleobases [113], oligonucleotides [114], and antibodies [115] to conducting polymers like polypyrrole and polythiophene [116]. However, conducting polymers with covalently bound ion-recognition sites seems to be a rather unexplored research area in terms of potentiometric ion sensors.…”
Section: Conducting Polymer-based Chemical Sensorsmentioning
confidence: 99%